Risk Management in the Omed-Omedan Cultural Festival in Sesetan, Bali (Unit Pelayanan Bahasa, Politeknik Pariwisata Bali, 2025)
The Omed-Omedan Festival, held annually in Banjar Kaja, Sesetan Village, Bali, is a unique cultural heritage event that emphasizes youth participation and social interaction. Despite its long-standing tradition and popularity among tourists, the festival faces several challenges in risk management, particularly concerning crowd control, safety, and health protocols. This study aims to analyze the implementation of risk management at the Omed-Omedan Festival based on the ISO 31000:2018 framework. The research employs a qualitative descriptive approach through observation, in-depth interviews, and documentation involving four key informants selected using the snowball sampling technique. The results reveal that although risk communication and identification have been conducted, the overall implementation of risk management remains suboptimal, especially in documentation, monitoring, and post-event evaluation. This study contributes to enhancing event safety practices and offers recommendations for improving the sustainability and management quality of traditional festivals in Bali.